2010
DOI: 10.1007/s10397-010-0573-4
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic myomectomy using endoscopic loops under progressive tension

Abstract: The Authors describe a novel technique for laparoscopic myomectomy of fibroids with a subserosal component which involves the use of endoscopic loops under progressive tension to avoid bleeding, facilitate enucleation and possibly reduce the need of conventional sutures. Data analysis from a series of 34 consecutive operations shows that the use of endoloops helps achieving a good haemostasis, and no case of haemorrhage from the fibroid bed was ever recorded. Moreover, the need of diathermy was reduced, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In case of myomectomies for intramural fibroids, intraoperative techniques to reduce bleeding, such as those by endoscopic loops or ligations [ 48 50 ], might be preferable over preoperative UAE [ 22 ]. Identification and separate suturing of different layers, especially in case of opening of the endometrial cavity, is recommendable.…”
Section: Discussionmentioning
confidence: 99%
“…In case of myomectomies for intramural fibroids, intraoperative techniques to reduce bleeding, such as those by endoscopic loops or ligations [ 48 50 ], might be preferable over preoperative UAE [ 22 ]. Identification and separate suturing of different layers, especially in case of opening of the endometrial cavity, is recommendable.…”
Section: Discussionmentioning
confidence: 99%
“…Intracorporeal or extracorporeal knots can be used if tension is maintained. Preformed disposable endoscopic loops can be used if a progressive tie can be realized ( 41 ). If enucleation is achieved, the endoloop is tied and offers mechanical hemostasis, as well as a good exposure of the cleavage plane.…”
Section: Types Of Suturesmentioning
confidence: 99%
“…If enucleation is achieved, the endoloop is tied and offers mechanical hemostasis, as well as a good exposure of the cleavage plane. Studies have shown a reduction in diathermy, thus improving scar quality ( 41 ). The “bottom-up suture” technique was proposed for better suturing by elevating the bed of the myoma while still attached to the uterus ( 42 ); advantages of this technique include hemorrhage control and prevention of dead-space formation.…”
Section: Types Of Suturesmentioning
confidence: 99%
“…For instance, commercial loops can be used successfully directly on the serosa and myometrium surrounding the base of subserosal fibroids (5). The application of such loops before the incision on the serosa, and their progressive tightening, reduces blood loss from perimyomatous vessels globally and also facilitates the enucleation thanks to a ''squeezing'' effect on the myometrium.…”
mentioning
confidence: 99%